Autism Case Report: Cause and Treatment of “High Opioid Tone” Autism - Anugu, Vishal; Ringhisen, John; Johnson, Brian (Frontiers in Psychology, 2021)
Introduction: Neurobiological systems engineering models are useful for treating patients. We show a model of “high opioid tone” autism and present a hypothesis about how autism is caused by administration of opioids during childbirth. Main Symptoms: Clinical diagnosis of autism in a 25 year old man was confirmed by a Social Responsiveness Scale (SRS) self-rating of 79, severe, and a Social Communications Questionnaire (SCQ-2) by the patient's father scoring 27. Cold pressor time (CPT) was 190 seconds—unusually long, consonant with the high pain tolerance of autism. Therapeutic Intervention and Outcomes: At naltrexone 50 mg/day SRS fell to 54 and SCQ-−2–9; both non-significant. CPT fell to 28, repeat 39 s. Improved relatedness was experienced ambivalently, understood as feelings never before experienced—causing pain. Non-compliance with naltrexone was followed by cutting open his palm and drinking alcoholically. Transference focused psychotherapy has helped him remain naltrexone—compliant while he works on issues of identity and relatedness. Conclusion: The model suggests studies that could be conducted to both prevent and treat this form of autism.